Apparent diffusion coefficient value for a B-cell central nervous system lymphoma in a cat. Issue 1 (January 2018) - Tanaka, Toshiyuki; Akiyoshi, Hideo; Shimazaki, Hitoshi; Kawakami, Ryo; Mie, Keiichiro; Yamada, Yuki; Ohashi, Fumihito
Case summary: This report involves a 10-year-old male mixed-breed cat with a B-cell central nervous system (CNS) lymphoma. The cat presented with ataxia progressing to left hemiparesis. While haematological findings were normal, serum biochemistry showed a high creatine phosphokinase concentration. MRI revealed a homogeneously enhancing well-demarcated extra-axial lesion involving the region of the left lateral aperture with oedema in left flocculus and left medulla oblongata. On diffusion-weighted imaging, the lesion margins showed marked hyperintensity relative to the right cerebellar hemisphere. On an apparent diffusion coefficient map, the lesion appeared hypointense, with an apparent diffusion coefficient value of 0.57 ± 0.01 × 10 −3 mm 2 /s. Cerebrospinal fluid (CSF) analysis and cytology, and genetic analysis of CSF lymphoblasts confirmed a diagnosis of B-cell lymphoma. The owner opted for palliative treatment with prednisolone (1 mg/kg q12h); however, the cat died of dyspnoea 10 days after presentation. Relevance and novel information: CNS lymphomas, which are the second most common intracranial tumours in cats, are highly infiltrative lesions and radical surgical excision is not recommended. Therefore, accurate diagnosis is crucial. However, contrast-enhanced MRI cannot always differentiate these lesions from other conditions, including other CNS tumours and strokes. To the best of our knowledge, this is the first report to document the diffusion-weighted imaging features and apparent diffusion coefficient value for a feline CNS lymphoma. These findings are expected to improve the diagnostic accuracy of these lesions in cats.